"Nossa! Nunca imaginei preparar uma aula desse jeito": os letramentos críticos na formação inicial de professores de língua inglesa - Patrícia Mara de Carvalho Costa Leite (2017)
The aim of this study is to investigate and produce new ways of understanding the opportunities to address critical literacies in a pre-service teacher education program at a federal university in Minas Gerais. To this end, the main question addressed in this study is as follows: How can critical literacies enable the expansion of perspectives (MONTE-MÓR, 2009) as well as provide a critical-reflective practice in a pre-service context? The participants include fourteen undergraduate students in a clinical teaching practice course. Through a collaborative action research within a qualitative approach to data analysis and discussion, this study presents some evidence on the need of a more critical-reflective approach and the expansion of perspectives within the university classroom. This is more evident when one considers the vital role that clinical teaching practice has on pre-service teacher education. On this basis, it is recommended more support to undergraduate students concerning new perspectives that can make the clinical teaching practice more relevant and appreciated. Moreover, the critical literacies approach proved to be instrumental in showing the participants other means of teaching/learning the English language at schools in order to promote citizenship.